2011
DOI: 10.1159/000332760
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Small Cell Carcinoma: A Case Report and Review of the Literature

Abstract: We present a rare case of small cell carcinoma of the rectum presenting with rectal bleeding and discomfort in a fit 51-year-old gentleman. Our patient was treated with a combination of chemotherapy and radiotherapy and remains alive and free of disease 6 years after diagnosis. Our patient experience and review of the literature is presented highlighting the uncertainties regarding the biological behaviour and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Neuroendocrine tumors of the GI tract often present with metastatic disease and thus generally carry a poor prognosis [7] . Prior case reports have shown that the disease is invariably fatal, and therapy is complex due to the rarity and limited reports describing effective treatment of these tumors [1] . In addition, many of these tumors have been found to have components of squamous cell carcinoma and adenocarcinoma, which further complicate treatment [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine tumors of the GI tract often present with metastatic disease and thus generally carry a poor prognosis [7] . Prior case reports have shown that the disease is invariably fatal, and therapy is complex due to the rarity and limited reports describing effective treatment of these tumors [1] . In addition, many of these tumors have been found to have components of squamous cell carcinoma and adenocarcinoma, which further complicate treatment [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Small-cell carcinoma of the rectum is a rare, aggressive neoplasm derived from neuroendocrine cells within the gastrointestinal (GI) tract [1] , [2] . Very few case reports of small-cell rectal carcinoma have been published, and available therapies are generally not very effective, with the disease generally carrying a poor prognosis [1] . We describe an unusual case of metachronous small-cell rectal carcinoma presenting on an 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) follow-up for follicular lymphoma.…”
Section: Introductionmentioning
confidence: 99%
“…Spiliopoulou et al . [7] reported a case in 2011 of a patient with an obstructing tumor in the lower rectum (limited disease) treated with a combination of chemotherapy and radiotherapy; this patient was disease-free 4.5 years after completion of the treatment. In 2004, Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Staging [7] and management [5] of GI tract SCC have been proposed and implemented in case reports and a few retrospective studies. The staging system was introduced by the Veteran’s Administrating Lung Study Group (VALSG) for primary SCC of the lung [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation